2-(3,5-Di-tert-butyl-4-hydroxybenzyl-sulfanyl)nicotinic acid - Ariffin, Azhar; Ng, S.W.; Mansor, S.; Yehye, W.A.; Rahman, N.A. (International Union of Crystallography, 2008)
Two molecules of the title compound, C(21)H(27)NO(3)S, are disposed about a center of inversion, generating an O-H center dot center dot center dot O hydrogen-bonded dimer.